INVISIBLE COLLEGE IN INTERDISCIPLINARY FIELDS: FOUCAULT IN ACCOUNTING RESEARCH - Mendonça Neto, Octavio Ribeiro de; Riccio, Edson Luiz; Sakata, Marici Cristine Gramacho; Cardoso, Ricardo Lopes; Quoniam, Luc Marie (Advances in Scientific and Applied Accounting, 2011)
Michel Foucault’s works have been referenced in several fields of knowledge and such influence has also been noticed in accounting. The objective of this paper is to find at what point in time Foucault’s work started to be used in accounting literature, how it was accepted or refused by researchers and identify invisible colleges. This study contributes to identify the development of a new area of research through the movements of theories between fields. It identifies how foucaultian researches have been utilized to explain power and disciplinary aspects in accounting. The first level of analysis is based on Bourdieu’s theory and descriptive research. A total of 68 accounting journals were analyzed and 123 articles with reference to Foucault were identified. 40% are based in his theory and 60% are incidental appropriation according to Chartier’s typology. The second level was a bibliometric analysis and revealed a significant presence of Foucault’s ideas in Critical Accounting and a productivity behavior according to Lotka’s Law. The third level of analysis is based on Social Network Theory. It aimed to identify invisible colleges dealing with this subject. Results showed a network of authors and journals in a more centralized position.